Analisis Sistem Pengendalian Internal Pengembangan Sistem Informasi Desa - Felicia Aurellia Hadiluwarso; Kezya Audela; Ika Kristianti (Universitas Kristen Satya Wacana Salatiga, 2021)
Information systems are expected to help securing assets and minimizing theft, destruction, and data loss. However, actions such as hacking and data theft are still rife because of the weak management of the organization's internal control system. Village Information System is a means to collect, process and communicate various information related to the state of the village so that the need for monitoring, identifying and analyzing periodically about how the function of the internal control system runs to minimize fraud and misuse of information in order to achieve organizational goals. This community service is a form of active participation of academics to help villages identify and evaluate internal controls that have been applied in developing village information systems effectively. With descriptive qualitative research methods using data triangulation analysis techniques with interviews to village officials, it is able to give the result that increasing village government knowledge about the importance of implementing internal control systems related to the efficient and effective use of village information systems to avoid and minimize risks that allow to occur.